Advanced approaches in lung cancer therapy–Exploring the unique role of Multiwalled Carbon Nanotubes - Pushpendra Kumar Khangar; Vivek Daniel (Next Nanotechnology)
Hypothesis: This paper hypothesizes that Multiwalled Carbon Nanotubes (MWCNTs) can serve as effective nanocarriers for anticancer drug delivery in lung cancer therapy. Their high surface area, biocompatibility, and adaptable surface chemistry make them promising candidates for enhancing drug delivery efficiency. MWCNTs offer the potential to enable targeted transport of anticancer drugs directly to lung cancer cells, reducing systemic toxicity through controlled and prolonged drug release while also improving drug clearance mechanisms. However, despite these advantages, the study acknowledges significant concerns regarding toxicity, biocompatibility, and long-term safety. Addressing these challenges is crucial for the successful clinical translation of MWCNT-based drug delivery systems. Experiments (review-based analysis): Although this study does not conduct direct experiments, it reviews existing research and experimental findings on the incorporation of anticancer drugs into Multiwalled Carbon Nanotubes (MWCNTs), which involves efficient loading and release methods that ensure drug stability and retention within the nanocarrier system. These approaches enhance the controlled delivery of therapeutic agents, preventing premature degradation and maximizing efficacy. MWCNTs play a crucial role in drug delivery by improving circulation, enabling controlled release, and minimizing systemic toxicity. Additionally, surface modifications of MWCNTs contribute to better drug delivery efficiency by enhancing solubility and targeting capabilities. However, concerns regarding safety and biocompatibility remain critical. Preclinical studies have been conducted to evaluate the toxicity, biodegradability, and inflammatory response associated with MWCNTs. Surface modifications have been explored as a strategy to mitigate adverse effects, improve cellular compatibility, and enhance the overall feasibility of MWCNT-based drug delivery systems for lung cancer therapy. Findings: MWCNT-based drug delivery demonstrates significant potential in improving lung cancer treatment by enabling targeted drug transport to cancer cells, thereby enhancing therapeutic efficacy. The controlled release of drugs from MWCNTs helps minimize systemic toxicity, ultimately improving patient safety and treatment outcomes. However, several challenges and limitations must be addressed before clinical implementation. Toxicity remains a primary concern, as MWCNTs may trigger inflammatory responses or accumulate in tissues, leading to potential long-term adverse effects. Additionally, the biocompatibility and overall safety of these nanocarriers require further validation through rigorous preclinical testing. Looking ahead, extensive research is essential to develop clinically viable MWCNT-based drug delivery systems. Further advancements in surface modifications and biodegradability enhancements are necessary to reduce toxicity and enhance clinical safety, paving the way for the successful integration of MWCNTs in lung cancer nanomedicine.